Customs and Tariff Regulation of Foreign Trade Operations in the EU Market - Kravchuk, Taras Viktorovych (Волинський національний університет імені Лесі Українки, 2025)
Customs regulations play a vital role in safeguarding a nation's economy by ensuring the lawful and efficient movement of goods across borders. They help generate substantial government revenue through tariffs and duties, protect domestic industries from unfair foreign competition, and prevent the influx of counterfeit or harmful products. Additionally, well-enforced customs policies contribute to national security by controlling the import and export of sensitive or restricted items. Customs regulations can be used as a tool to foster economic stability, enhance competitiveness, and support sustainable economic growth. The EU uses customs tariffs to implement a unified customs and trade policy, build a common market, and protect its economic interests. The Common Customs Tariff supports trade policy and provides economic aid to developing countries. Key steps toward the Customs Union included eliminating internal duties, harmonizing indirect taxes, introducing uniform external tariffs, and removing internal trade barriers. These actions accelerated the creation of the EU’s single currency and advanced economic integration. A characteristic feature of the common trade policy of the EU based on this analysis can be called internal liberalism, as well as significant external protectionism. One of the priority areas of the EU's trade policy is the further development of trade, market expansion, integration of developing countries and underdeveloped countries into it through their support and assistance, but at the same time, the EU clearly establishes requirements for such countries, their goods, and, in particular, for the implementation of economic and social reforms by them.
Keywords: duty; tariff; regulation; European Union; trade; agreement; politics